ANALISIS KINERJA KARYAWAN PADA KOPERASI TELKOMSEL CABANG PONTIANAK - B31108146, HARUN (Jurnal Manajemen Update, 2013)
This research describes how the performance of employees in the Telkomsel Cooperation Branch Pontianak. This research aims to determine the performance of employees in the Telkomsel Cooperation Branch Pontianak. This research is conducted using descriptive method and the techniques of data collection are questionnaires, interviews and documentary studies. The population in this research is by thirty employees of the Telkomsel Cooperation Branch Pontianak. The sampling is conducted with census method and techniques of data analysis is analysis of qualitative descriptive and equipped with information from questionnaires answered by the repondent. Answers are tabulated and presented in the from of tables and presented in percentages to take the conclusion as background for answering this problem. The statistical variable and research are quality, quantity, timelinees, cost effectiveness, need for supervision, inter-personal impact. Based on the findings, the overall performance of employees working at the Telkomsel Coorperation Branch Pontianak has been achieved well